Marine biotechnology : evaluation and development of methods for the discovery of natural products from fungi - Pather, Simisha (Rhodes University, Faculty of Pharmacy, Pharmacy, 2005)
One of the major impediments in the development of marine natural products is the provision of biologically active natural products in sufficient quantity for complete pharmacological evaluation, clinical trials and eventual commercial production. Marine microorganisms show great promise in providing a renewable source of biologically active natural products. The main aim of this study was to develop and evaluate methods for the isolation, identification and cultivation of marine fungi from the South African marine environment for the production of biologically active secondary metabolites. Twenty-four species of fungi were isolated from marine algae collected from the intertidal zone near Port Alfred, South Africa. The fungi were cultivated in small-scale under static and agitated conditions and their crude intra- and extracellular organic extracts were screened by Â¹H NMR and a series of bioassays. Using this as a basis, one isolate was selected for further study. By analyses of the lTS1 region of the ribosomal DNA, the fungal isolate was identified as a marine-derived isolate of Eurotium rubrum (Aspergillus ruber). Although E. rubrum has been isolated from the marine environment, no investigations have been undertaken to determine the adaptation of these isolates to the marine environment. In order to optimise productivity, creativity and incubation time, the fungus was cultivated in small-scale using a variety of carbon (glucose, fructose, lactose, sucrose, marmitol and maltose) and nitrogen sources (ammonium tartrate, urea, peptone and yeast extract). An HPLC-DAD method was developed to assess the metabolic creativity and productivity under different fermentation conditions. Distinctive variations in the range and yield of metabolites produced as well as morphology and growth time were observed. The crude extracts from all fermentations were combined and six known compounds were isolated by reversed-phase chromatography and their structures elucidated by spectroscopic techniques. The known compounds were fIavoglaucin, aspergin, isodihydroauroglaucin, isotetrahydroauroglaucin, neoechinuline A and physcion. Neoechinuline A, isodihydroauroglaucin and isotetrahydroauroglaucin showed activity against oesophageal and cervical cancer cell lines.
Keywords: Marine biotechnology; Marine fungi -- South Africa; Natural products -- South Africa; Marine plants -- South Africa; Marine metabolites -- South Africa; Cancer -- Treatment; DNA